Do Lithuanian employers need multilingual employees? - Kalninytė, Agnė (Kalbotyra, 2011)
This paper discusses the variety of languages and the level of language competence required in job advertisements in Lithuania. The research is based on the data collected from on-line and hard-copy newspapers; job advertisements under investigation include those written in Lithuanian and other languages. The main findings suggest that in on-line advertisements employers require foreign language competence more often than those in the hard-copy adverts. It has also been observed that competence of two languages is of high demand. If employers require competence of 3 languages, the order of the languages is as follows: national (Lithuanian), lingua-franca (English), and others (Russian or Polish). Lithuanian is of high importance in job advertisements as employers tend to take into consideration the level of written and spoken Lithuanian. Finally, the data have revealed that in job advertisements language knowledge is described in very abstract terms, and references to the CEFR are hardly ever observed in the collected data.